SCREENING AND CHARACTERIZATION OF SOIL FUNGAL ISOLATES FOR INHIBITING THE GROWTH OF Ganoderma boninense - Haqqa, Zhafira Amila; Rupaedah, Bedah; Handayani, Indri; Wahid, Abdul; Sugianto, Mahmud (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
Ganoderma boninense, a fungus recognized as a causative agent of basal stem rot and upper stem rot, is primarily found in oil palm plantations (Elaeis guineensis Jack.). This study aimed to identify soil fungal isolates with the greatest potential for inhibiting the pathogenic fungus G. boninense. The research employed curative antagonist testing using in vitro dual culture. Fungal isolates demonstrating the highest inhibition percentages were characterized through macroscopic and microscopic observation, and their hemolysis properties were assessed using blood agar media. Soil fungal isolates FA 3.8 and FA 2.8 exhibited the highest inhibition percentages, reaching 91% and 88%, respectively. Based on morphological characterization at both macroscopic and microscopic levels, FA 3.8 displayed similarities to Trichoderma, while FA 2.8 exhibited similarities to Penicillium. Hemolysis testing results on blood agar media indicated that both isolates exhibited gamma hemolysis or non-hemolysis, as they lacked red blood lysis properties.